A Chiral Secondary Amine–Amidophosphane Precatalyst for Silver-Catalyzed Asymmetric 1,3-Dipolar Cycloaddition Reactions - Zheng, Xiaojun; Deng, Qifu; Hou, Qinglin; Zhang, Kaiqiang; Wen, Pushan; Hu, Shunqin; Wang, Haifei (Synthesis, 2018)
A class of multifunctional amidophosphanes derived from chiral 1,2-diphenylethylenediamines and natural α-amino acids has been developed. Among these, in combination with silver(I) salts, a chiral secondary amine–amidophosphane precatalyst has been demonstrated as being a highly efficient multifunctional precatalyst in the asymmetric 1,3-dipolar cycloaddition of azomethine ylides, including a series of heterocyclic, aliphatic, and 2-substituted azomethine ylides, and aromatic α,β-unsaturated aldehyde derived imino esters with different electron-deficient alkenes, as well as the three-component reaction of α-imino esters generated in situ by using N,N′-diisopropylcarbodiimide as dehydrating agent. Under optimal conditions, highly functionalized endo-adducts were obtained in high to excellent yields (up to 99% yield) and enantioselectivities (up to >99.9% ee).
Keywords: secondary amine; amidophosphanes; silver carbonate; 1,3-dipolar cycloaddition; pyrrolidines